Correction to: Risk factors for developing severe COVID-19 in China: an analysis of disease surveillance data - Meng-Jie Geng; Li-Ping Wang; Xiang Ren; Jian-Xing Yu; Zhao-Rui Chang; Can-Jun Zheng; Zhi-Jie An; Yu Li; Xiao-Kun Yang; Hong-Ting Zhao; Zhong-Jie Li; Guang-Xue He; et al. (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.